The relationship between the expression pattern of starch biosynthesis enzymes and molecular structure of high amylose maize starch. (1st November 2020) - Zhong, Yuyue; Liu, Linsan; Qu, Jianzhou; Li, Silu; Blennow, Andreas; Seytahmetovna, Shayakhmetova Altyn; Liu, Xingxun; Guo, Dongwei
Highlights: A high-amylose maize (HAM) mutant locus showed different molecular structure than the canonical amylose extender mutant. HAM starches showed high content of long amylopectin chains (DP > 21). HAM starches had increased proportion of short amylose chains. The mutant had low expression on SBEIIb and SSIIIa, and high expression on ISA2. Abstract: Two high amylose (HAM) inbred lines with apparent amylose contents of 55 % and 62 %, respectively, were selected to explore the relationship between molecular structure and gene expression of starch-synthase involved enzymes. GPC analysis of debranched starches showed that the HAM starches (HAMSs) had shorter amylose chains and longer amylopectin chains than normal maize starch (NMS). FACE analysis showed that these HAMSs had a higher content of amylopectin chains of DP > 21. Quantitative Real-Time PCR analysis showed that the HAM lines had specifically low expression of the starch branching enzyme IIb (SBEIIb), and the starch synthase IIIa (SSIIIa) homologue, and high expression of the isoamylase 2 (ISA2), potentially suppressing the generation of amylopectin molecules through deficient branching and excessive debranching process, thereby increasing the relative amylose content. A high expression of GBSS1 was potentially associated with increased short amylose chain lengths in HAMSs.